2023
DOI: 10.1007/s43450-023-00409-3
|View full text |Cite
|
Sign up to set email alerts
|

Safflor Yellow A Protects Beas-2B Cells Against LPS-Induced Injury via Activating Nrf2

Abstract: Acute lung injury and its severe form acute respiratory distress syndrome are lethal lung diseases. So far, effective therapy for the diseases is deficient and the prognosis is poor. Recently, it was found activating nuclear factor erythroid 2-related factor 2 could attenuate the injury including inflammation, oxidative stress, and apoptosis in those diseases. To discover novel therapy, we have evaluated safflor yellow A and explored the underlying mechanisms using Beas-2B cells injured by lipopolysaccharide. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…In this experiment, Western blotting showed that the protein expression of nuclear factor erythroid 2-related factor 2 (Nrf2) was noticeably upregulated in the Cis/Bact A and/or Cis/Bact B group mice ( Figure 6 A,B), suggesting that Bact A and/or Bact B might have a potential for life-protection by attenuating oxidative stresses and/or inflammatory injury via the regulation of the Nrf2 signaling pathway [ 17 ]. However, the protein expression of heme oxygenase 1 (Ho-1) was not so much upregulated, either in the Cis/Bact A or in the Cis/Bact B group mice ( Figure 6 A,C).…”
Section: Resultsmentioning
confidence: 99%
“…In this experiment, Western blotting showed that the protein expression of nuclear factor erythroid 2-related factor 2 (Nrf2) was noticeably upregulated in the Cis/Bact A and/or Cis/Bact B group mice ( Figure 6 A,B), suggesting that Bact A and/or Bact B might have a potential for life-protection by attenuating oxidative stresses and/or inflammatory injury via the regulation of the Nrf2 signaling pathway [ 17 ]. However, the protein expression of heme oxygenase 1 (Ho-1) was not so much upregulated, either in the Cis/Bact A or in the Cis/Bact B group mice ( Figure 6 A,C).…”
Section: Resultsmentioning
confidence: 99%
“…The inflammatory response plays an important role in ARDS, and the increased release of proinflammatory factors and the relatively insufficient amount of anti-inflammatory factors in the early stage of ARDS are the main mechanisms leading to an uncontrolled inflammatory response in ARDS 34 36 . A previous study showed that the lung tissue of LPS-induced ARDS model rats exhibited increased infiltration of polymorphonuclear leukocytes (PMNs), which produce and release many inflammatory factors, including IL-1α, IL-1β, IL-4, IL-6, IL-10, and TNF-α 37 . Among them, TNF-α, as the initiating factor of ARDS, represents the severity of the inflammatory response in the early stage of ARDS 38 .…”
Section: Discussionmentioning
confidence: 99%